2018
DOI: 10.1172/jci99169
|View full text |Cite
|
Sign up to set email alerts
|

Itaconic acid mediates crosstalk between macrophage metabolism and peritoneal tumors

Abstract: Control of cellular metabolism is critical for efficient cell function, although little is known about the interplay between cell subset–specific metabolites in situ, especially in the tumor setting. Here, we determined how a macrophage-specific (Mϕ-specific) metabolite, itaconic acid, can regulate tumor progression in the peritoneum. We show that peritoneal tumors (B16 melanoma or ID8 ovarian carcinoma) elicited a fatty acid oxidation–mediated increase in oxidative phosphorylation (OXPHOS) and glycolysis in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
170
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(173 citation statements)
references
References 53 publications
2
170
1
Order By: Relevance
“…In addition, it was recently reported that the mitochondrial metabolite itaconate activates NRF2-dependent transcription through alkylation of KEAP1 on C151, C257, C273, C288, and C297. Although a role for itaconate has been identified in peritoneal tumors, studies examining the interplay between itaconate, KEAP1, and NRF2 hyperactivation in cancer have not yet been reported (110,111). Recently, Bollong and colleagues identified a new PTM for KEAP1, methylimidazole crosslink between proximal cysteine and arginine residues (MICA; ref.…”
Section: V334 S363mentioning
confidence: 99%
“…In addition, it was recently reported that the mitochondrial metabolite itaconate activates NRF2-dependent transcription through alkylation of KEAP1 on C151, C257, C273, C288, and C297. Although a role for itaconate has been identified in peritoneal tumors, studies examining the interplay between itaconate, KEAP1, and NRF2 hyperactivation in cancer have not yet been reported (110,111). Recently, Bollong and colleagues identified a new PTM for KEAP1, methylimidazole crosslink between proximal cysteine and arginine residues (MICA; ref.…”
Section: V334 S363mentioning
confidence: 99%
“…A very recent study into the role of IRG1 and itaconate in tumor progression revealed that IRG1 promotes tumor progression through crosstalk between macrophages and tumor cells . In a cancer setting, IRG1 was shown to promote macrophage‐derived mitochondrial ROS which amplifies mitogen‐activated protein kinase (MAPK) activation in a paracrine fashion in neighboring tumor cells.…”
Section: Tca Cycle In Macrophage Polarizationmentioning
confidence: 99%
“…A very recent study into the role of IRG1 and itaconate in tumor progression revealed that IRG1 promotes tumor progression through crosstalk between macrophages and tumor cells. 72 In a cancer setting, IRG1 was shown to promote macrophage-derived mitochondrial ROS which amplifies mitogen-activated protein kinase (MAPK) activation in a paracrine fashion in neighboring tumor cells. While this finding that IRG1, and presumably itaconate, promote macrophage mitochondrial ROS is in agreement with a previous study, 73 they are in apparent contradiction with other studies where itaconate was found to actively suppress mitochondrial ROS.…”
Section: Aconitate/itaconatementioning
confidence: 99%
“…Tissues such as the peritoneal cavity are frequently the site of tumor development and metastasis, and as such there is considerable potential crosstalk between developing tumors and tissue‐resident macrophages that normally play important roles in homeostasis and immune surveillance. We recently showed that crosstalk between tumor cells and resident macrophages of the peritoneum induces metabolic alterations in the resident macrophage population, which in turn regulates macrophage effector function and tumor progression . In ovarian carcinoma, which metastasizes to and grows progressively in the peritoneum, altered metabolite expression is highlighted by the dramatic up‐regulation of the metabolite, itaconic acid, in resident macrophages .…”
Section: Functional Diversity In Phagocytic Cellsmentioning
confidence: 99%
“…We recently showed that crosstalk between tumor cells and resident macrophages of the peritoneum induces metabolic alterations in the resident macrophage population, which in turn regulates macrophage effector function and tumor progression . In ovarian carcinoma, which metastasizes to and grows progressively in the peritoneum, altered metabolite expression is highlighted by the dramatic up‐regulation of the metabolite, itaconic acid, in resident macrophages . Itaconic acid was already recognized as an important metabolite due to its ability to inhibit the glyoxylate shunt, an anabolic variation of the TCA that is essential for bacterial growth .…”
Section: Functional Diversity In Phagocytic Cellsmentioning
confidence: 99%